2010
DOI: 10.1113/jphysiol.2010.194035
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and AMPK cooperatively regulate PGC-1α in skeletal muscle cells

Abstract: Nitric oxide (NO) induces mitochondrial biogenesis in skeletal muscle cells via upregulation of the peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α). Further, we have shown that nitric oxide interacts with the metabolic sensor enzyme, AMPK. Therefore, we tested the hypothesis that nitric oxide and AMPK act synergistically to upregulate PGC-1α mRNA expression and stimulate mitochondrial biogenesis in culture. L6 myotubes treated with nitric oxide donors, S-nitroso-N -penicillamine (SNAP, 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 63 publications
6
136
0
1
Order By: Relevance
“…This indicates that that NO signalling is both upstream and downstream of AMPK and CaMK, respectively. Similar findings were demonstrated by Lira et al (2010), where pharmacological inhibition of AMPK attenuated PGC-1α mRNA expression, despite co-treatment with NO donors. It was also shown that PGC-1α mRNA expression was attenuated when muscle cells were treated with NOS inhibitor, L-NAME despite co-treatment with AICAR.…”
Section: Nitric Oxidesupporting
confidence: 82%
See 1 more Smart Citation
“…This indicates that that NO signalling is both upstream and downstream of AMPK and CaMK, respectively. Similar findings were demonstrated by Lira et al (2010), where pharmacological inhibition of AMPK attenuated PGC-1α mRNA expression, despite co-treatment with NO donors. It was also shown that PGC-1α mRNA expression was attenuated when muscle cells were treated with NOS inhibitor, L-NAME despite co-treatment with AICAR.…”
Section: Nitric Oxidesupporting
confidence: 82%
“…1) (Lira et al, 2010;McConell et al, 2010). In a recent study, McConell et al (2010) showed that AMPK and CaMK were activated in L6 myocytes treated with NO donors, in line with increased protein expressions of PGC-1α, COX1 and COX4.…”
Section: Nitric Oxidementioning
confidence: 96%
“…PGC-1␣ expression is increased in response to nitric oxide in an AMPKdependent fashion (30). Following exposure to exogenous nitric oxide, PGC-1␣ is increased in wild-type (WT) MEFs, while nitric oxide-induced expression of PGC-1␣ is absent in IRE1␣ Ϫ/Ϫ cells (Fig.…”
Section: Nitricmentioning
confidence: 99%
“…In turn, PGC-1a is transcriptionally regulated by p-CREB, which promotes PGC-1a expression in the presence of cold and fasting stimulus (27). Besides that, the transcriptional activity of PGC-1a is also modulated by post-translational modifications, e.g., deactivation by SIRT1 and phosphorylation by AMPK (28,29). AMPK is switched on by an increase of AMP-ATP ratio, which results in AMPK phosphorylation.…”
Section: Dysfunction Of Mitochondrial Biogenesis Is Highly Involved Imentioning
confidence: 99%